2018
DOI: 10.3389/fmats.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Low Fatigue Dynamic Auxetic Lattices With 3D Printable, Multistable, and Tuneable Unit Cells

Abstract: Stress distribution has led to the design of both tough and lightweight materials. Truss structures distribute stress well and are commonly used to design lightweight materials for applications experiencing low strains. In 3D lattices, however, few structures allow high elastic compression and tunable deformation. This is especially true for auxetic material designs, such as the prototypical re-entrant honeycomb with sharp corners, which are particularly susceptible to stress concentrations. There is a pressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 53 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…An S-hinged unit cell design, as shown in Fig. 8 was proposed by Khare et al [143]. The design derives its inspiration from the common re-entrant cell design, which permits an easier tuneability and stability of the unit cells along with lower fatigue damage.…”
Section: Common Auxetic Structures and Their Prominent Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…An S-hinged unit cell design, as shown in Fig. 8 was proposed by Khare et al [143]. The design derives its inspiration from the common re-entrant cell design, which permits an easier tuneability and stability of the unit cells along with lower fatigue damage.…”
Section: Common Auxetic Structures and Their Prominent Characteristicsmentioning
confidence: 99%
“…The structures exhibit a uniform elastic behavior in all principal directions while Fig. 8 Unit cell structure of an S-hinged unit cell [143] Fig. 9 Double-V unit cell structure [144] Fig.…”
Section: Common Auxetic Structures and Their Prominent Characteristicsmentioning
confidence: 99%
“…Lattice structures can exhibit unusual properties by rationally arranging or adjusting their microstructures (Bertoldi et al, 2017). Among them, tunable Poisson's ratio is of particular interest (Fozdar et al, 2011;Ai and Gao 2017;Chen et al, 2017;Khare et al, 2018;Liu and Zhang. 2018;de Jongeet al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other significant architectures include the anti-chiral structures studied by Alderson et al [66] along with Pozniak and Wojciechowski [67] in addition to shape-preserving structures [68,69], and various composites [70,71]. Despite this, Zadpoor [72] found that studies in metals have been limited to beam-based architecture [73][74][75][76] with much less information on plate/sheet/walled/surface − architecture.…”
Section: Introductionmentioning
confidence: 99%